1972
DOI: 10.1111/j.1471-0528.1972.tb14192.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cortisol and Adrenocorticotrophic Hormone in Normal Men and Non‐pregnant Women, Normal Pregnant Women and Women With Pre‐eclampsia

Abstract: Summary Determinations of plasma cortisol and adrenocorticotrophic hormone (ACTH) have been made in normal men and non‐pregnant women, in normal pregnant women and women with pre‐eclampsia, in maternal and cord blood during normal vaginal delivery and during delivery by Caesarean section. The findings in normal individuals, including the demonstration of diurnal variations, are in agreement with those of other workers, thus validating the methodology used. In pregnancy the plasma cortisol is raised and ACTH lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Kopelman and Levitz (1970) observed that the mean maternal plasma cortisol concentration is normal pregnancy and pregnancy complicated by PET was not significantly different. Mukherjee and Swyer (1972) showed that pregnancies complicated by PET were associated with raised maternal plasma ACTH levels and reduced maternal cortisol levels compared with uncomplicated pregnancies, the authors suggesting that the maternal adrenal gland in PET may be relatively unresponsive to ACTH stimulation. Transplacental transfer of ACTH cannot be ruled out under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Kopelman and Levitz (1970) observed that the mean maternal plasma cortisol concentration is normal pregnancy and pregnancy complicated by PET was not significantly different. Mukherjee and Swyer (1972) showed that pregnancies complicated by PET were associated with raised maternal plasma ACTH levels and reduced maternal cortisol levels compared with uncomplicated pregnancies, the authors suggesting that the maternal adrenal gland in PET may be relatively unresponsive to ACTH stimulation. Transplacental transfer of ACTH cannot be ruled out under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Growth hormone responses were measured by radioimmunoassay (Hartog et al, 1963), and cortisol responses by the fluorimetric method of Mattingly (1962). Plasma ACTH levels were measured by the radioimmunoassay technique described by Berson and Yalow (1968) using a modification by Mukherjee and Swyer (1972), the antibody being specific against N terminal 1-24 ACTH and synthetic human 1-39 ACTH.…”
mentioning
confidence: 99%
“…Thus hypophysectomy causes adrenal hypoplasia [Liggins and Kennedy, 1968] and prolongs gestation [Liggins et al, 1967], Both effects can be overcome by ACTH in fusion [Liggins, 1969]. In man, several pituitary hormones are released by the fetal pituitary at the time of birth since elevated levels of ACTH [Berson and Yalow, 1968;M ukherjee and Swyer, 1972; Ratcliffe and Chard, unpubl. ], AVP [Hoppenstein et al, 1968] and oxytocin [Chard et al, 1971] are found in umbilical cord blood during delivery, the levels being higher in the umbilical artery than the vein.…”
Section: Introductionmentioning
confidence: 99%